2020
DOI: 10.1097/md.0000000000022390
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins concentration and B cell counts as severity markers in adult community-acquired pneumonia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…Increase of WBC count together with lymphocyte decrease in patients with CAP compared to healthy controls, especially those with sCAP, indicates the natural response to severe infection, which is consistent with previous studies [ 10 , 13 ]. We found that compared to CAP, sCAP was characterized by significantly lower absolute number of B cells, PBMC, Bn cells and Btr cells, significantly lower PBMC subset percentage, as well as percentage of naïve B cells, while percentage of IgM + Bm cells was significantly higher.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increase of WBC count together with lymphocyte decrease in patients with CAP compared to healthy controls, especially those with sCAP, indicates the natural response to severe infection, which is consistent with previous studies [ 10 , 13 ]. We found that compared to CAP, sCAP was characterized by significantly lower absolute number of B cells, PBMC, Bn cells and Btr cells, significantly lower PBMC subset percentage, as well as percentage of naïve B cells, while percentage of IgM + Bm cells was significantly higher.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, percentage of IgM + Bm cells was significantly higher in CAP and especially sCAP compared to healthy controls. However, other reports indicate that total blood IgM, IgG2 and IgG levels are lower in CAP [ 10 ], as well as some other inflammatory and autoimmune diseases [ 23 ]. This contradiction seems to be related to the previously reported defect in some IgM + Bm cells, which upon re-stimulation with a T cell-dependent antigen fail to differentiate into IgM antibody-secreting cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T lymphocyte counts in the critical and severe groups are significantly lower than those in the mild groups ( p < 0.01). A negative correlation is shown between immune response and severity, similar to other reports ( Lei et al, 2020 ; Luchsinger et al, 2020 ). The absolute number of B lymphocytes and T lymphocytes from COVID-9 patients may be closely related to the severity of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies on the association of serum Ig levels with pneumonia prevalence and severity in immunocompetent individuals reported inconclusive results and were performed in adults with a heterogeneous age range ( 12 – 16 ). These studies furthermore had several limitations that potentially restrict extrapolation of results to older individuals from a general population.…”
Section: Introductionmentioning
confidence: 99%